Rethinking growth and survival of hospitality industry in Jordan: the role of responsible and resilient leadership styles in managing crisis - Raed Hussam Alzoubi; Baker Shnaikat; Maisoon Abo Murad; Rami Al kloub; Ma'en Alhmesat; Omar Hamdan Mohammad Alkharabsheh (Cogent Business & Management, 2024)
The crisis in Jordan has had disastrous effects on the national economy, particularly impacting the hospitality sector. Confronted with dramatic uncertainty, hospitality leaders must rapidly nurture responsibility and resilience. To enhance our understanding of how responsible and resilient leadership responds to such shocks, we aim to investigate if responsible and resilient leadership styles can foster crisis management in the hospitality sector through the mediating path of knowledge management, and the moderating role of digital transformation using the conservation of resources (COR) theory to support our hypotheses. This theory asserts that organizational resources facilitate effective crisis management, implying that adequate resources and support systems enable organizations to navigate and recover from crises effectively. Data was gathered from 154 owners and senior managers in the hospitality sector, and the proposed relationships were evaluated using partial least squares structural equation modeling (PLS-SEM). These findings imply that responsible and resilient leadership styles significantly influence crisis management. Furthermore, knowledge sharing mediates the relationship between these leadership styles and effective crisis management. Finally, the study identifies digital transformation as a significant moderator between knowledge sharing and crisis management. This research contributes to the existing literature on leadership and crisis management by demonstrating that, during times of crisis, leadership characterized by responsibility and resilience enhances crisis management within the hospitality sector.
Keywords: 650; Leadership styles; crisis management; digital transformation; knowledge sharing; hospitality firms'; COR theory; Jordan